Emergency medical service mobile application for emergency, radiology, and pathology departments in hospital Pekan - Low, Ching Chuan (2014)
This project review is about an Android mobile application developed to solve the issues that communicate between emergency department, radiology department, and pathology department. In this project, Emergency Medical Service Mobile Application's objective is to manage the data transaction between different departments and develop a prototype mobile application for 3 different departments to improve their data transaction. Methodology used in this project is waterfall model that consists of 5 phases include planning, analysis, design, implementation, and maintenance. Therefore, through the development of this Emergency Medical Service Mobile Application, it helps 3 departments have better communication and data transferring in more convenient way and easy to manage.